Incidence of sudden cardiac death in adults with end-stage renal disease: a systematic review and meta-analysis. Issue 1 (December 2016) - Ramesh, Sharanya; Zalucky, Ann; Hemmelgarn, Brenda; Roberts, Derek; Ahmed, Sofia; Wilton, Stephen; Jun, Min
Abstract Background Although sudden cardiac death (SCD) is recognized as a distinct cause of death in patients with end stage renal disease (ESRD), its incidence has not been well summarized. Methods We performed a systematic review and meta-analysis of the literature based on a protocol developeda priori . We searched MEDLINE and EMBASE (inception to March 2015) for randomized controlled trials and cohort studies reporting the incidence of SCD in adult patients with ESRD on hemodialysis or peritoneal dialysis. We collected data on number of SCD as well as the definition of SCD for each individual study. A random-effects model was used to summarize the incidence of SCD. We conducted subgroup analyses to explore sources of heterogeneity. Results Forty two studies (n  = 80, 382 patients) were included in the meta-analysis. The incidence of SCD among adults with ESRD ranged from 0.4 to 10.04 deaths per 100 person-years. The definitions and assessment of SCD varied across the included studies. There was evidence of significant heterogeneity (I2  = 98;p  < 0.001), which was not explained by subgroup analyses stratified by mean age, proportion of hypertensive or diabetic patients, follow-up time, study size, or type of cohort studied. Conclusion Current estimates of the incidence of SCD among adults with ESRD vary widely. There is a need for further studies to more accurately estimate the incidence of SCD in patients with ESRD.